Determining priority strategies for chili agribusiness development through an integrated strategic analysis framework in Tolitoli District, Indonesia - RILWANU RAHMAN ALATAS; ABDUL RAZAK MUNIR; ABD HARIS BAHRUN (Smujo International, 2026)
Abstract. Alatas RR, Munir AR, Bahrun AH. 2026. Determining priority strategies for chili agribusiness development through an integrated strategic analysis framework in Tolitoli District, Indonesia. Asian J Agric 10 (1): g100160. https://doi.org/10.13057/asianjagric/g100160. Chili pepper (Capsicum spp.) is a strategic horticultural commodity in Indonesia due to its high consumption level and significant influence on food price stability. In Tolitoli District, despite favorable agroclimatic conditions, chili productivity remains substantially below the provincial average (1.14 ton ha compared with 6.43 ton ha at the provincial level in 2023), while recurring price volatility contributes to regional inflation, reaching 7.21% year-on-year in 2024. These challenges are associated with weak farmer institutions, limited bargaining power, and fragmented agribusiness integration. This study aims to analyze internal and external factors, formulate alternative development strategies, and determine priority strategies for chili agribusiness development in Tolitoli District. A descriptive-exploratory mixed-methods approach was employed, integrating qualitative and quantitative data collected from key stakeholders. Data were analyzed sequentially using the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Grand Strategy Matrix, and SWOT analysis, followed by prioritization using the Analytical Hierarchy Process (AHP). The results indicate that chili agribusiness development is positioned in Quadrant I of the Grand Strategy Matrix, reflecting a strong competitive position and high growth potential. Institutional support emerges as the most influential criterion in determining strategic priorities. The development of area-based chili production centers, aligned with land potential and market demand, is identified as the top priority strategy. The AHP results demonstrate acceptable consistency, with a consistency ratio (CR) below the threshold of 0.10. These findings highlight the importance of strengthening institutional coordination and promoting integrated, cluster-based agribusiness development to enhance competitiveness, stabilize prices, and ensure long-term sustainability of chili agribusiness in Tolitoli District.